Choledochal Stenting for Treatment of Extrahepatic Biliary Obstruction in Dogs with Ruptured Gallbladder: 2 Cases - Shin-Ho Lee; Jeong-Hyun Seo; Jae-Hyeon Cho (Veterinary Sciences)
Two geriatric (>9 years old) dogs presented with vomiting, depression, and anorexia and were diagnosed with extrahepatic biliary obstruction (EHBO) secondary to ruptured gallbladder mucoceles. Diagnosis was based on serum biochemical analysis, abdominal radiography, and ultrasonography, which revealed gallbladder rupture, peritonitis, and common bile duct dilation. Both dogs underwent emergency surgical intervention involving cholecystectomy and choledochal stent placement in the common bile duct without cholecystojejunostomy or cholecystoduodenostomy. Postoperatively, the clinical symptoms and serum chemistry values improved, and both dogs survived without recurrence for over one year. These cases demonstrate that choledochal stenting can be an effective adjunct to cholecystectomy for managing EHBO in dogs with ruptured gallbladder mucoceles, potentially preventing reocclusion and promoting recovery, especially when histopathological evaluation is not feasible in clinical settings. However, persistent elevation of liver enzymes may occur postoperatively, necessitating prolonged monitoring and medical management in some cases.